Empowering Girls: Role of Cyanobacteria Spirulina in Nourishing Growth and Vitality - Dubey , Anuradha (Asian Journal of Pharmaceutical Research and Development, 2024)
This study is performed to explore the potential of Spirulina in empowering girls by enhancing their growth and vitality. However adolescent girls often face nutritional deficiencies due to various socio-economic factors compromising their health and well-being. Spirulina, a nutrient-rich microalga emerges as a promising solution due to its rich nutritional profile and easy cultivation. This study is exploring the nutritional benefits of Spirulina, highlighting its high protein content, essential vitamins, minerals and antioxidants. Moreover, it examines Spirulina’s potential in addressing prevalent health issues among girls such as iron deficiency anemia and malnutrition. Furthermore the study discusses the feasibility and sustainability of integrating Spirulina into girls’ diets through various interventions, including supplementation programs and community-based initiatives. By leveraging Spirulina’s nutritional ability, adolescent girls can be empowered to flourish, ensuring a brighter and healthier future for generations to come.